Microbial production of bioactive retinoic acid using metabolically engineered escherichia coli - Han, Minjae; Lee, Pyung Cheon (Microorganisms, 2021)
Microbial production of bioactive retinoids, including retinol and retinyl esters, has been successfully reported. Previously, there are no reports on the microbial biosynthesis of retinoic acid. Two genes (blhSR and raldhHS) encoding retinoic acid biosynthesis enzymes [β‐carotene 15,15’‐ oxygenase (Blh) and retinaldehyde dehydrogenase2 (RALDH2)] were synthetically redesigned for modular expression. Co‐expression of the blhSR and raldhHS genes on the plasmid system in an engineered β‐carotene‐producing Escherichia coli strain produced 0.59 ± 0.06 mg/L of retinoic acid after flask cultivation. Deletion of the ybbO gene encoding a promiscuous aldehyde reductase induced a 2.4‐fold increase in retinoic acid production to 1.43 ± 0.06 mg/L. Engineering of the 5’‐ UTR sequence of the blhSR and raldhHS genes enhanced retinoic acid production to 3.46 ± 0.16 mg/L. A batch culture operated at 37 °C, pH 7.0, and 50% DO produced up to 8.20 ± 0.05 mg/L retinoic acid in a bioreactor. As the construction and culture of retinoic acid–producing bacterial strains are still at an early stage in the development, further optimization of the expression level of the retinoic acid pathway genes, protein engineering of Blh and RALDH2, and culture optimization should synergistically increase the current titer of retinoic acid in E. coli.
Keywords: Metabolic engineering; Retinaldehyde dehydrogenase; Retinoic acid; Retinoid; β‐carotene 15,15’‐oxygenase